Gradient of zinc content in core–shell zinc ferrite nanoparticles – precise study on composition and magnetic properties. Issue 42 (16th October 2019) - Lachowicz, Dorota; Wirecka, Roma; Górka-Kumik, Weronika; Marzec, Mateusz Marek; Gajewska, Marta; Kmita, Angelika; Żukrowski, Jan; Sikora, Marcin; Zapotoczny, Szczepan; Bernasik, Andrzej
Abstract : Structure, magnetic properties and chemical composition of synthesized zinc ferrite nanoparticles were characterized by a broad spectrum of methods. Abstract : A broad spectrum of applications of magnetic nanoparticles leads to the need for the precise tuning of their magnetic properties. In this study, a series of magnetite and zinc-ferrite nanoparticles were successfully prepared by modified high-temperature synthesis in a controlled gas atmosphere. Nanoparticles with different zinc to iron ratios and pure Fe3 O4 were obtained. The structure of the nanoparticles was studied by transmission electron microscopy and Mössbauer spectroscopy. These revealed the single domain character of the nanoparticles and the influence of the synthesis temperature and zinc to iron ratio on their shape and size. Chemical structure was characterized by inductively coupled plasma optical emission spectroscopy, energy dispersive X-ray spectroscopy and thermogravimetric analysis. X-ray photoelectron spectroscopy coupled with an argon gas cluster ion beam (Ar-GCIB) allowed the study of subsequent layers of the nanoparticles without altering their chemical structure. This revealed the presence of a carbon layer on all nanoparticles consisting of capping agents used in the synthesis and revealed the core–shell character of the zinc ferrite particles. In addition, different types of zinc infusions in the nanoparticle structure were observed when using different Zn/Fe ratios. Finally, magnetic studies performed by means of vibrating sample magnetometry proved the superparamagnetic behavior of all the samples.